Piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nano composite material as well as preparation method and application of piezoelectric enhanced photocatalytic coating
ZnO/BiOCl nanocomposites were prepared by hydrothermal method and applied to the surface of cement-based materials. The piezoelectric enhancement technology was used to improve the photocatalytic degradation ability, solving the low efficiency and complex production problems of existing photocatalytic cement-based materials, and achieving efficient self-cleaning and corrosion resistance.
Patent Information
- Application Number
- CN202510058908.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-05-02
AI Technical Summary
The existing preparation methods for photocatalytic cement-based materials have problems such as large amount of photocatalyst, low efficiency, and complex production, and it is difficult to effectively remove contaminants on the surface of cement-based materials, affecting their corrosion resistance.
The ZnO/BiOCl nanocomposite was prepared by hydrothermal method, and its photocatalytic degradation ability was improved through piezoelectric enhancement technology, and the coating was prepared and applied to the surface of cement-based material to achieve self-cleaning and corrosion resistance.
It improves the photocatalytic degradation performance and cycle stability of cement-based materials, enhances its self-cleaning ability and corrosion resistance, and extends its service life.
Smart Images

Figure CN119909708A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a piezoelectric enhanced photocatalytic coating based on a ZnO / BiOCl nanocomposite material, and a preparation method and application thereof. Background Art
[0002] As an important building material, cement-based materials have the advantages of high compressive strength, good durability, convenient production methods, and low production costs. They are widely used in the construction of infrastructure such as buildings, bridges, roads, marine engineering, and rivers. However, due to the complex service environment, its surface is easily corroded by pollutants, which deteriorates the durability of the cement-based material, thereby affecting the safety and stability of its structure and shortening its service life. Applying acrylates, polyurethanes, chlorinated rubbers, and epoxy resins to the surface of cement-based materials can effectively block pollutants from contacting the surface of cement-based materials, thereby improving the corrosion resistance of its structure. However, coating the surface of cement-based materials can passively improve their corrosion resistance and hydrophobicity, but cannot effectively remove surface pollutants. Therefore, how to give the surface of cement-based materials a cleaning and purification effect and improve their corrosion resistance has become a hot research issue in the current field of building materials.
[0003] Applying photocatalysts to cement-based materials can give them the effects of pollutant degradation and surface self-cleaning, reduce the corrosion probability of buildings with cement-based materials as the main materials, extend service life and improve durability. At present, the commonly used preparation methods for photocatalytic cement-based materials are mainly direct internal mixing method, aggregate loading method and surface coating method. The amount of photocatalyst used in the direct internal mixing method is large, and the opacity of the cement matrix leads to waste of photocatalyst and low photocatalytic efficiency. The aggregate loading method is complicated and not easy to mass produce, and the compatibility of the photocatalyst with the cement matrix needs to be considered. The surface coating method can not only reduce the amount of photocatalyst and improve the photocatalytic efficiency, but more importantly, its preparation process is simple and easy. In addition, the surface coating method mostly uses resins as the dispersion medium, which can effectively improve the surface hydrophobicity and further enhance its self-cleaning performance. Therefore, the surface coating method can give cement-based materials a surface cleaning and purification effect and enhance its corrosion resistance, becoming a research hotspot in the current field of building materials. The efficient conversion of solar energy through photocatalytic technology has great potential for alleviating the current energy crisis and the increasingly serious environmental pollution, but the unsatisfactory conversion efficiency still hinders its practical application. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the prior art and provide a piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite materials. ZnO / BiOCl nanocomposite materials can utilize mechanical energy introduced through external fields such as wind energy, tidal energy, and ultrasound in nature to enhance their ability to photocatalytically degrade organic pollutants, showing excellent photocatalytic degradation performance and cycle stability, and showing excellent application prospects in purifying water bodies, improving water quality, etc. The present invention also provides a method for preparing the piezoelectric enhanced photocatalytic coating based on the ZnO / BiOCl nanocomposite materials, and the application of coating the piezoelectric enhanced photocatalytic coating on the surface of cement-based materials.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A method for preparing a piezoelectric enhanced photocatalytic coating based on a ZnO / BiOCl nanocomposite material specifically comprises the following steps:
[0007] Step 1: Preparation of ZnO nanomaterials by hydrothermal method:
[0008] Mix 1 part of zinc acetate dihydrate and citric acid in a mass ratio of 4:3 evenly, add to 40-60 parts of deionized water, then add 10-15 parts of anhydrous ethanol dropwise, and stir to fully dissolve it; then, slowly add 4.0-6.0 mol / L sodium hydroxide solution dropwise to adjust its pH value to 10-12; finally, transfer the obtained suspension to a reactor, keep it at 160-200°C for 20-24 hours, and after cooling, centrifuge and dry it to obtain ZnO nanopowder.
[0009] Step 2: Preparation of ZnO / BiOCl nanocomposites:
[0010] The obtained ZnO nanopowder is added to an excess of deionized water and ultrasonically dispersed for 20 to 40 minutes, and then BiCl3 is added at a molar ratio of ZnO to BiCl3 of 1:(2-6), stirred for 1 to 3 hours, and then centrifuged to obtain a precipitate. The obtained precipitate is dried to obtain a ZnO / BiOCl nanocomposite material.
[0011] Step 3: Preparation of ZnO / BiOCl-based coating:
[0012] The obtained ZnO / BiOCl nanocomposite material is added to anhydrous ethanol, and then polydimethylsiloxane is added thereto after ultrasonic dispersion for 20 to 40 minutes, and then ultrasonic dispersion is performed for another 20 to 40 minutes, and stirring is performed until the anhydrous ethanol is completely evaporated. A curing agent is added and stirring is continued until the rotor stops rotating automatically due to the increase in viscosity of the stirring system, and a ZnO / BiOCl-based coating is obtained, and then the obtained coating is applied to the surface of the substrate material to form a piezoelectric enhanced photocatalytic coating.
[0013] Preferably, in step 1 and step 2, the drying conditions are both 60-100° C. for 8-16 hours.
[0014] Preferably, in steps 1 to 3, magnetic stirring is used for stirring.
[0015] Preferably, the stirring speed in step 2 is 500-700 rpm.
[0016] Preferably, in step 3, the dosage of ZnO / BiOCl nanocomposite material is 1-5% of the mass of polydimethylsiloxane, and the coating amount of the obtained coating on the surface of the substrate material is 0.5-0.8 kg / m 2 .
[0017] A piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite material prepared by the method.
[0018] The invention discloses an application of a piezoelectric enhanced photocatalytic coating based on a ZnO / BiOCl nanocomposite material, wherein the obtained coating is applied to the surface of a cement-based material to form a piezoelectric enhanced photocatalytic coating.
[0019] Beneficial effects of the present invention: The present invention combines ZnO and BiOCl to form a pn junction, which can not only reduce the recombination probability of electron-hole pairs, but also effectively improve the photocatalytic degradation ability by introducing external field mechanical energy. The ZnO / BiOCl nanocomposite material is prepared into a coating and applied to the surface of the cement-based material to form a coating with self-cleaning performance, which can improve its corrosion resistance and durability without changing the internal structure of the cement-based material, thereby improving its service life; at the same time, driven by mechanical energy such as wind energy, tidal energy, and ultrasound in the environment where the cement-based material is located, the ZnO / BiOCl nanocomposite material can release electrons and holes, convert mechanical energy into electrical energy, thereby further improving the photocatalytic degradation ability of the coating, accelerating the degradation of pollutants in the surrounding water, and improving the self-cleaning effect of its own surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] FIG1 : X-ray powder diffraction patterns of the ZnO / BiOCl nanocomposite material and ZnO and BiOCl monomer nanomaterials prepared by the present invention.
[0021] Figure 2A : Ultraviolet diffuse reflectance images of the ZnO / BiOCl nanocomposite material and ZnO and BiOCl monomer nanomaterials prepared by the present invention.
[0022] Figure 2B :: Energy band structure diagram of the ZnO / BiOCl nanocomposite material prepared by the present invention.
[0023] Figure 3A : Photocatalytic degradation effect diagram of the ZnO / BiOCl nanocomposite material prepared by the present invention and ZnO and BiOCl monomer nanomaterials on MB solution.
[0024] Figure 3B : The piezoelectric photocatalytic degradation effect diagram of the ZnO / BiOCl nanocomposite material prepared by the present invention and the ZnO and BiOCl monomer nanomaterials on MB solution.
[0025] Figure 4A : (a) to (e) are the ultra-depth-of-field surface images of the piezoelectrically enhanced photocatalytic coating based on ZnO monomer nanomaterials, BiOCl monomer nanomaterials, and nanocomposite materials with molar ratios of ZnO to BiCl3 of 1:2, 1:4, and 1:6, respectively.
[0026] Figure 4B :(f)~(j) are 3D renderings of piezoelectrically enhanced photocatalytic coatings based on ZnO monomer nanomaterials, BiOCl monomer nanomaterials, and nanocomposites with molar ratios of ZnO to BiCl3 of 1:2, 1:4, and 1:6, respectively.
[0027] Figure 5A : The photocatalytic degradation effect diagram of the piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite material prepared by the present invention, the coating based on ZnO monomer nanomaterial, and the coating based on BiOCl monomer nanomaterial on MB solution.
[0028] Figure 5B : The piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite prepared by the present invention, the coating based on ZnO monomer nanomaterial, and the coating based on BiOCl monomer nanomaterial on the piezoelectric photocatalytic degradation effect of MB solution.
[0029] Figure 5C : Graph showing the cyclic piezoelectric photocatalytic degradation effects of the piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite materials, the coating based on ZnO monomer nanomaterials, and the coating based on BiOCl monomer nanomaterials on MB solution prepared by the present invention.
[0030] Fig. 6A : (a) to (e) are the surface wetting properties of the piezoelectrically enhanced photocatalytic coating before degrading MB solution, respectively, based on ZnO monomer nanomaterials, BiOCl monomer nanomaterials, and nanocomposite materials based on ZnO and BiCl3 with a molar ratio of 1:2, 1:4, and 1:6.
[0031] Figure 6B: (f) to (j) are the surface wetting properties of the piezoelectrically enhanced photocatalytic coating after degradation of MB solution, which are based on ZnO monomer nanomaterials, BiOCl monomer nanomaterials, and nanocomposite materials with a molar ratio of ZnO to BiCl3 of 1:2, 1:4, and 1:6, respectively. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] The cement paste test blocks used in the examples and comparative examples of the present invention were prepared by the following process:
[0034] 100 g of standard cement and 36 g of water were first mixed and stirred at a rotation speed of 60 rpm for 100 s, and then mixed and stirred at a rotation speed of 150 rpm for 100 s to obtain cement slurry; the prepared cement slurry was then poured into a mold and vibrated to form, and a cement slurry test block was obtained after curing for 7 days.
[0035] Example 1
[0036] Preparation of ZnO / BiOCl Nanocomposites :
[0037] Step 1: Preparation of ZnO nanomaterials by hydrothermal method: 4.8 g of zinc acetate dihydrate and 3.6 g of citric acid were weighed and added to 60 mL of deionized water, and then 18 mL of anhydrous ethanol was added dropwise and stirred at 500 rpm until uniform; then, 5.0 mol / L of sodium hydroxide solution was slowly added dropwise to adjust the pH value to 11; finally, the obtained suspension was transferred to a hydrothermal reactor with a volume of 100 mL and placed in an oven at 180°C for 22 h; after the reactor was cooled, it was centrifuged and dried to obtain a white powder sample, which was the ZnO nanopowder.
[0038] Step 2: Add the obtained ZnO nanopowder into 30 mL of deionized water and ultrasonically disperse it for 30 min, then quickly add BiCl3 at a molar ratio of ZnO to BiCl3 of 1:2, magnetically stir at a speed of 600 rpm for 1 h, and then centrifuge to obtain a precipitate. After drying the obtained precipitate at 80°C for 12 h, a ZnO / BiOCl nanocomposite material with a composite ratio of 1:2 can be obtained.
[0039] Preparation of cement-based coating based on ZnO / BiOCl nanocomposite :
[0040] 0.17 g of the prepared ZnO / BiOCl nanocomposite was added to 20 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. Then, 7.5 g of PDMS was added to the suspension and ultrasonically dispersed for another 30 min. Then, the suspension was stirred until the anhydrous ethanol was completely evaporated. Finally, 0.75 g of curing agent was added and stirring was continued until the rotor stopped rotating due to the increased viscosity of the stirring system. The prepared slurry was immediately heated to 0.65 kg / m 2 The amount of the coating was applied to the surface of the cement paste specimen and allowed to stand at room temperature for 24 hours to form a piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite materials on the surface of the cement paste specimen after it was fully dried.
[0041] Example 2
[0042] Preparation of ZnO / BiOCl Nanocomposites :
[0043] Step 1: Preparation of ZnO nanomaterials by hydrothermal method: 4.8 g of zinc acetate dihydrate and 3.6 g of citric acid were weighed and added to 60 mL of deionized water, and then 18 mL of anhydrous ethanol was added dropwise and stirred at 500 rpm until uniform; then, 5.0 mol / L of sodium hydroxide solution was slowly added dropwise to adjust the pH value to 11; finally, the obtained suspension was transferred to a hydrothermal reactor with a volume of 100 mL and placed in an oven at 180°C for 22 h; after the reactor was cooled, it was centrifuged and dried to obtain a white powder sample, which was the ZnO nanopowder.
[0044] Step 2: Add the obtained ZnO nanopowder into 30 mL of deionized water and ultrasonically disperse it for 30 min, then quickly add BiCl3 at a molar ratio of ZnO to BiCl3 of 1:4, magnetically stir at a speed of 600 rpm for 1 h, and then centrifuge to obtain a precipitate. After drying the obtained precipitate at 80°C for 12 h, a ZnO / BiOCl nanocomposite material with a composite ratio of 1:4 can be obtained.
[0045] Preparation of cement-based coating based on ZnO / BiOCl nanocomposite :
[0046] 0.17 g of the prepared ZnO / BiOCl nanocomposite was added to 20 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. Then, 7.5 g of PDMS was added to the suspension and ultrasonically dispersed for another 30 min. Then, the suspension was stirred until the anhydrous ethanol was completely evaporated. Finally, 0.75 g of curing agent was added and stirring was continued until the rotor stopped rotating due to the increased viscosity of the stirring system. The prepared slurry was immediately heated to 0.65 kg / m 2 The amount of the coating was applied to the surface of the cement paste specimen and allowed to stand at room temperature for 24 hours to form a piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite materials on the surface of the cement paste specimen after it was fully dried.
[0047] Example 3
[0048] Preparation of ZnO / BiOCl Nanocomposites :
[0049] Step 1: Preparation of ZnO nanomaterials by hydrothermal method: 4.8 g of zinc acetate dihydrate and 3.6 g of citric acid were weighed and added to 60 mL of deionized water, and then 18 mL of anhydrous ethanol was added dropwise and stirred at 500 rpm until uniform; then, 5.0 mol / L of sodium hydroxide solution was slowly added dropwise to adjust the pH value to 11; finally, the obtained suspension was transferred to a hydrothermal reactor with a volume of 100 mL and placed in an oven at 180°C for 22 h; after the reactor was cooled, it was centrifuged and dried to obtain a white powder sample, which was the ZnO nanopowder.
[0050] Step 2: Add the obtained ZnO nanopowder into 30 mL of deionized water and ultrasonically disperse it for 30 min, then quickly add BiCl3 at a molar ratio of ZnO to BiCl3 of 1:6, magnetically stir at a speed of 600 rpm for 1 h, and then centrifuge to obtain a precipitate. After drying the obtained precipitate at 80°C for 12 h, a ZnO / BiOCl nanocomposite material with a composite ratio of 1:6 can be obtained.
[0051] Preparation of cement-based coating based on ZnO / BiOCl nanocomposite :
[0052] 0.17 g of the prepared ZnO / BiOCl nanocomposite was added to 20 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. Then, 7.5 g of PDMS was added to the suspension and ultrasonically dispersed for another 30 min. Then, the suspension was stirred until the anhydrous ethanol was completely evaporated. Finally, 0.75 g of curing agent was added and stirring was continued until the rotor stopped rotating due to the increased viscosity of the stirring system. The prepared slurry was immediately heated to 0.65 kg / m 2 The amount of the coating was applied to the surface of the cement paste specimen and allowed to stand at room temperature for 24 hours to form a piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite materials on the surface of the cement paste specimen after it was fully dried.
[0053] Comparative Example 1
[0054] Preparation of ZnO Monomer Nanomaterials :
[0055] Preparation of ZnO nanomaterials by hydrothermal method: 4.8 g of zinc acetate dihydrate and 3.6 g of citric acid were weighed and added to 60 mL of deionized water, and then 18 mL of anhydrous ethanol was added dropwise and stirred at 500 rpm until uniform; then, 5.0 mol / L of sodium hydroxide solution was slowly added dropwise to adjust the pH value to 11; finally, the obtained suspension was transferred to a hydrothermal reactor with a volume of 100 mL and placed in an oven at 180°C for 22 h; after the reactor was cooled, it was centrifuged and dried to obtain a white powder sample, which was the ZnO nanopowder.
[0056] Preparation of cement-based coating based on ZnO monomer nanomaterials :
[0057] 0.17 g of the prepared ZnO monomer nanomaterial was added to 20 mL of anhydrous ethanol, and ultrasonically dispersed for 30 min. Then, 7.5 g of PDMS was added to the suspension, and ultrasonically dispersed for another 30 min. Then, the suspension was stirred until the anhydrous ethanol was completely evaporated. Finally, 0.75 g of curing agent was added and stirring was continued until the rotor stopped rotating due to the increased viscosity of the stirring system. The prepared slurry was immediately heated to 0.65 kg / m 2 Apply the amount of the coating to the surface of the cement paste test block, let it stand at room temperature for 24 hours to form a coating based on ZnO monomer nanomaterials on the surface of the cement paste test block after it is fully dried.
[0058] Comparative Example 2
[0059] Preparation of BiOCl Monomer Nanomaterials :
[0060] 3.40 g of BiCl3 was added to 30 mL of deionized water, and the mixture was vigorously stirred at 500 rpm for 1 h. The mixture was then centrifugally washed twice with deionized water and anhydrous ethanol. The resulting precipitate was dried at 80° C. for 12 h to obtain BiOCl monomer nanomaterials.
[0061] Preparation of cement-based coating based on BiOCl monomer nanomaterials :
[0062] 0.17 g of the prepared BiOCl monomer nanomaterial was added to 20 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. Then, 7.5 g of PDMS was added to the suspension and ultrasonically dispersed for another 30 min. Then, the suspension was stirred until the anhydrous ethanol was completely evaporated. Finally, 0.75 g of curing agent was added and stirring was continued until the rotor stopped rotating due to the increased viscosity of the stirring system. The prepared slurry was immediately heated to 0.65 kg / m 2 The amount of the coating was applied to the surface of the cement paste specimen, and allowed to stand at room temperature for 24 hours to form a coating based on BiOCl monomer nanomaterials on the surface of the cement paste specimen after it was fully dried.
[0063] The nanomaterials and coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were characterized for their relevant properties. The relevant characterization methods, instruments, etc. are as follows:
[0064] 1. X-ray diffractometer (copper target, scanning range 3-70 °, scanning step 0.02, Rigaku Corporation, model D / MAX-Ultima IV), scanning electron microscope (voltage 2kV, Japan HITACHI company, model HitachiS4800) were used to characterize the crystal structure and microscopic morphology of the sample. The LAMBDA750 UV-visible-near infrared spectrophotometer produced by PerkinElmer Co., Ltd. was used to test the band structure of the sample (scanning range 200-800nm). An ultrasonic cleaner (Shanghai Shangpu Instrument Co., Ltd., model SN-QX-32, power 220W) was used to provide mechanical action for the sample to verify its piezoelectric degradation ability. A xenon lamp cold light source (Anhui Langxi Bobei Lighting Appliance Co., Ltd., model BBZM-I, power 300W) was used to simulate sunlight for photocatalytic degradation experiments. The absorbance of the sample photocatalytic degradation experimental solution was tested using a UV-visible photometer (Shanghai Yidian Analytical Instrument Co., Ltd., model 721G). The surface morphology of the coating was analyzed by Leica DM6M ultra-depth microscope and the flatness of the coating was analyzed by ultra-depth electron microscope (Keyence, Japan, model VHX-600K). The wetting properties of the coating were evaluated by contact angle meter (Shanghai Zhongchen Digital Technology Equipment Co., Ltd., JC2000DM).
[0065] 2. Catalytic performance test:
[0066] A xenon lamp was used as a simulated light source, an ultrasonic cleaner provided mechanical vibration, and methylene blue MB (10 mg / L) was selected as the target pollutant for degradation.
[0067] For nanomaterial powder samples: weigh 0.05 g of powder sample and put it into 50 mL of 10 mg / L methylene blue solution. Take out 10 mL of the sample every 20 minutes, centrifuge and take the supernatant, and measure the absorbance at a wavelength of 664 nm.
[0068] For coating samples: the coated cement paste specimens were placed in 100 mL of 10 mg / L methylene blue solution; during the photocatalytic degradation process, 10 mL of sample was taken out every hour for absorbance measurement, and during the piezoelectric photocatalysis with mechanical vibration provided by an ultrasonic cleaner, 10 mL of sample was taken out every 20 minutes for absorbance measurement.
[0069] The degradation efficiency η is calculated using the following formula:
[0070] η=[(c0-c t ) / c0]×100%
[0071] Where C0 represents the initial absorbance, C t Represents the absorbance at a certain time.
[0072] Analyze the performance characterization results in combination with the attached figures:
[0073] Depend on Figure 1A It can be seen that the diffraction peaks of ZnO and BiOCl are sharp, and no other impurity peaks appear, corresponding to ZnO (PDF#36-1451) and BiOCl (PDF#06-0249), respectively, indicating that this method can be used to prepare ZnO and BiOCl with good crystallinity. Figure 1B It can be seen that all peaks are sharp, the half-peak width is narrow, and there are no other impurity peaks, indicating that the sample has high purity and good crystallinity. Obvious diffraction peaks appear at 12.0°, 24.1°, 25.9°, 32.5°, etc., corresponding to the characteristic diffraction peaks of BiOCl (PDF#06-0249), confirming that the sample contains BiOCl with good crystallinity. Due to the relatively small amount of ZnO and the acidic environment caused by the hydrolysis of BiCl3, some ZnO will be dissolved, resulting in the absence of the characteristic diffraction peak of ZnO in the curve.
[0074] Figure 2A and Figure 2B The UV diffuse reflectance and band structure diagrams of ZnO / BiOCl nanocomposites and ZnO and BiOCl monomer nanomaterials are shown respectively. The maximum absorption wavelengths of ZnO / BiOCl nanomaterials with composite ratios of 1:2, 1:4, and 1:6 are 398nm, 384nm, and 388nm, which are better than the maximum absorption wavelength of pure BiOCl (379nm), but smaller than the maximum absorption wavelength of pure ZnO (419nm). The band gaps calculated using the Tauc plot method show that the band gaps of pure ZnO and BiOCl are 3.04eV and 3.23eV. The band gaps of ZnO / BiOCl nanomaterials with composite ratios of 1:2, 1:4, and 1:6 are 3.06eV, 3.12eV, and 3.09eV, respectively. Compared with pure BiOCl, the band gap of ZnO / BiOCl nanomaterials is significantly narrowed. This is because BiOCl and ZnO have matching band positions, which promotes the separation of electrons and holes. At the same time, when ZnO was compounded with BiOCl in different proportions, it was found that the band gap of ZnO / BiOCl-1:2 nanomaterials was the narrowest, showing a higher separation rate of photogenerated electrons and holes; while the band gap of ZnO / BiOCl-1:4 nanomaterials was the widest, indicating that its separation rate of electrons and holes was lower, but still better than BiOCl. Therefore, when BiOCl and ZnO in different proportions are compounded, their light response ability is significantly better than BiOCl.
[0075] Figure 3A and Figure 3BThe photocatalytic degradation effect diagram and piezoelectric photocatalytic degradation effect diagram of MB solution of ZnO / BiOCl nanocomposite materials and ZnO and BiOCl monomer nanomaterials are shown respectively. Due to the narrow band gap of ZnO, its photocatalytic degradation efficiency (35.6%) is higher than that of BiOCl (25.9%). The photocatalytic degradation efficiency of methylene blue of ZnO / BiOCl with different composite ratios is 52.8%, 37.8% and 46.9%, respectively, which is significantly improved compared with monomer ZnO and BiOCl. Among them, when ZnO:BiOCl is 1:2, the sample has the best photocatalytic degradation effect on MB, followed by 1:6, and the worst effect is 1:4. When light and ultrasonic vibration are applied simultaneously, the piezoelectric photocatalytic degradation efficiency of pure ZnO and BiOCl is 46.5% and 65%, respectively, which is 1.31 times and 2.51 times higher than the degradation efficiency of light alone, respectively, which fully shows that the piezoelectric enhanced photocatalytic degradation effect of BiOCl is more significant. The degradation efficiencies of ZnO / BiOCl-1:2, ZnO / BiOCl-1:4, and ZnO / BiOCl-1:6 were 80.5%, 75.7%, and 87.0%, which were 1.73, 1.63, and 1.87 times higher than those of ZnO monomer materials, indicating that the combination of the two can effectively improve their piezoelectric enhanced photocatalytic degradation performance. In addition, compared with the degradation efficiency of light alone, the piezoelectric enhanced photocatalytic degradation efficiency of ZnO / BiOCl-1:2, ZnO / BiOCl-1:4, and ZnO / BiOCl-1:6 was also increased by 1.52, 2.00, and 1.86 times, indicating the effectiveness of the piezoelectric enhanced photocatalytic performance caused by ultrasonic vibration.
[0076] Figure 4A and 4BThe super depth of field surface images and 3D effect images of piezoelectric enhanced photocatalytic coatings based on ZnO monomer nanomaterials, BiOCl monomer nanomaterials, and nanocomposites with a molar ratio of ZnO to BiCl3 of 1:2, 1:4, and 1:6, respectively. Small bubbles appeared inside the coating made by dispersing ZnO in PDMS, and it can be clearly seen that some powders are highly agglomerated. This is because the ZnO rhombic sheet structure has a large particle size and is unevenly dispersed. At the same time, the average height difference of its 3D image is relatively large, which once again confirms this result. Compared with ZnO nanomaterials, BiOCl is relatively uniformly dispersed inside the matrix, without bubbles and agglomerations, and its height difference is relatively small. In the cement-based material coating based on ZnO / BiOCl-1:2, the nanomaterial still has a small amount of agglomeration, but its flatness is better than that of the monomer material. When the BiOCl dosage continues to increase, its agglomeration effect is improved. When ZnO:BiOCl=1:6, its dispersion effect is the best. Therefore, with the increase of BiOCl dosage, its dispersibility is significantly improved. At the same time, the coating flatness is improved, and the average height difference is small.
[0077] Figure 5A , 5B Figures 5C and 5C are piezoelectric enhanced photocatalytic coatings based on ZnO / BiOCl nanocomposites, coatings based on ZnO monomer nanomaterials, and coatings based on BiOCl monomer nanomaterials for the piezoelectric photocatalytic degradation of MB solution. During the entire photocatalytic process, the degradation efficiencies of ZnO and BiOCl were 25.3% and 30.2%, respectively. The photocatalytic degradation efficiencies of methylene blue with different composite ratios of ZnO / BiOCl were 45.4%, 36.3%, and 38.5%, respectively, which were improved compared to monomers of ZnO and BiOCl. Among them, when the coating was coated with ZnO:BiOCl at a ratio of 1:2, the sample had the best photocatalytic degradation effect on MB, followed by a ratio of 1:6, and the worst effect was achieved with a ratio of 1:4, which was consistent with the effect of the powder. Figure 5BAs shown in the figure, when ultrasonic vibration and light are applied, the piezoelectric photocatalytic degradation efficiency of ZnO and BiOCl is 30.1% and 56.7%, which is 1.19 and 1.88 times higher than the degradation efficiency of light alone. The degradation efficiency of ZnO / BiOCl-1:2, ZnO / BiOCl-1:4, and ZnO / BiOCl-1:6 is 74.8%, 68.1%, and 81.1%. Compared with the ZnO monomer material, it is 2.49, 2.26, and 2.69 times higher. This shows that the piezoelectric photocatalytic effect of the composite coating is better than that of monomer ZnO. In addition, compared with the degradation efficiency of light alone, the piezoelectric enhanced photocatalytic degradation efficiency of ZnO / BiOCl-1:2, ZnO / BiOCl-1:4, and ZnO / BiOCl-1:6 coatings is also increased by 1.65, 1.88, and 2.11 times. Therefore, under the synergistic effect of piezoelectricity and light, the transfer rate of electrons increases and the amount of holes generated increases, thereby increasing its degradation efficiency. Figure 5C The cyclic stability test results of the cement-based material coating based on ZnO / BiOCl-1:6 are shown in the figure. As can be seen from the figure, after the coating has been degraded for 5 cycles, its stability is still maintained at about 80%, which fully proves that the coating has good stability.
[0078] Fig. 6A and 6B The surface wetting performance diagrams of the piezoelectric enhanced photocatalytic coating before and after the degradation of MB solution are respectively based on the coating of ZnO monomer nanomaterials, the coating based on BiOCl monomer nanomaterials, and the nanocomposite material based on the molar ratio of ZnO to BiCl3 of 1:2, 1:4, and 1:6. The PDMS coating without the addition of nanomaterials shows a certain hydrophobicity, and its contact angle is 101°. When the nanomaterials are dispersed in PDMS, the contact angles of the coatings prepared are improved. This is because the addition of nanomaterials forms a certain micro-nano structure on the surface of the coating, resulting in a relative increase in its roughness, thereby improving the hydrophobicity. When ZnO / BiOCl-1:6 is added, the contact angle of the coating reaches 113°. In order to explore whether its contact angle can stably maintain hydrophobicity, the contact angle of the coating was improved after a piezoelectric photocatalytic degradation experiment. The contact angle of the ZnO / BiOCl-1:6 coating reached 115°. This is mainly because under ultrasonic drive, the nanomaterials inside the coating are gradually squeezed and closer to its surface, which increases the contact area between the internal nanomaterials and the outside world, makes its micro-nano structure more prominent, and further increases the surface roughness, thereby improving its hydrophobic properties.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite material, characterized in that: The specific steps include: Step 1: Preparation of ZnO nanomaterials: 1 part of zinc acetate dihydrate and citric acid in a mass ratio of 4:3 are mixed evenly, added to 40-60 parts of deionized water, and then 10-15 parts of anhydrous ethanol are added dropwise, and stirred until uniform; then, 4.0-6.0 mol / L sodium hydroxide solution is slowly added dropwise to adjust the pH value to 10-12; finally, the obtained suspension is transferred to a reactor, kept at 160-200°C for 20-24 hours, and after cooling, centrifuged and dried to obtain ZnO nanopowder; Step 2: Preparation of ZnO / BiOCl nanocomposites: The obtained ZnO nanopowder is added to an excess of deionized water and ultrasonically dispersed for 20 to 40 minutes, and then BiCl3 is added at a molar ratio of ZnO to BiCl3 of 1:(2-6), stirred for 1 to 3 hours, and centrifuged to obtain a precipitate. The obtained precipitate is dried to obtain a ZnO / BiOCl nanocomposite material; Step 3: Preparation of ZnO / BiOCl-based coating: The obtained ZnO / BiOCl nanocomposite material is added to anhydrous ethanol, ultrasonically dispersed for 20 to 40 minutes, and then polydimethylsiloxane is added thereto, and ultrasonically dispersed for another 20 to 40 minutes, and then stirred until the anhydrous ethanol is completely volatilized. A curing agent is added and stirring is continued until the rotor stops rotating automatically due to the increase in viscosity of the stirring system, and a ZnO / BiOCl-based coating is obtained, and then the obtained coating is applied to the surface of the substrate material to form a piezoelectric enhanced photocatalytic coating.
2. The method for preparing a piezoelectric enhanced photocatalytic coating based on a ZnO / BiOCl nanocomposite material according to claim 1, characterized in that: In step 1 and step 2, the drying conditions are both drying at 60-100° C. for 8-16 hours.
3. The method for preparing a piezoelectric enhanced photocatalytic coating based on a ZnO / BiOCl nanocomposite material according to claim 1, characterized in that: In step 1 to step 3, magnetic stirring is used for stirring.
4. The method for preparing a piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite material according to claim 1, characterized in that: The stirring speed in step 2 is 500-700 rpm.
5. The method for preparing a piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite material according to claim 1, characterized in that: In step 3, the amount of ZnO / BiOCl nanocomposite material added is 1-5% of the mass of polydimethylsiloxane, and the coating amount of the obtained coating on the surface of the substrate material is 0.5-0.8 kg / m 2 .
6. A piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite material prepared by the method according to any one of claims 1 to 5.
7. An application of the piezoelectric enhanced photocatalytic coating based on ZnO / BiOCl nanocomposite material according to claim 6, characterized in that: The obtained coating is applied on the surface of cement-based materials to form a piezoelectric enhanced photocatalytic coating.